Aplicación de cianamida hidrogenada para la homogenización del brotamiento de la vid (Vitisvinifera) en Cascas - Siguas Díaz, Oscar Daniel (2011)
The grapeinrecentyearshasbecomethelargestexportcropwitheconomic growth, increasing by 61%areasinstalledin differentparts of the regiontobea profitable cropandbroadoutput window forthe United States andEurope.This fact isforcingproducersto obtain abetter quality fruitand increased production. Thiswork was carried outresearchwith the aim ofdetermining the efficiency ofhydrogencyanamideinthesproutingof grapevine (Vitisvinifera), through the descriptionof results obtained byfieldsurveys and assessments.Thisstudy was conducted inCascasdistrict, province of GranChimu, which is located inthe middle ofthe river basinto 1274maslChicama, with an average annualclimatebetween17.44° C to27.30° C, which hasaverydiversifiedculturecedula, housing over 2,000 hectaresirrigatedbytheriverhelmets, whichare suitable foragriculture, especiallythe planting ofgrapes.We surveyed50growersin the area,inordertorescuetheirexperiencesfirst-handfield, applying hydrogen cyanamidein terms ofdoses,frequency, mode,season, etc.., Resulting in adisagreementof the winein front of thenon-uniformityofsproutingcausedbythe short timethe plant getspost-harvestand the dosagesand application materialsunsuitable.Similarly,assessments were conducted infieldsnewlysproutinginprunedandvisibleleafphenology, widespread and visibleclusters. The first evaluation wasbetween 14and 21DAAofcyanamide, while the second7 dayslater, iebetween 21and 28DAA,respectively, obtaining the number of budsperplant,sproutingComparative- production andvigorof an outbreak.Therefore thiscurrentidentificationofgrapecultivationopeningusmany possibilities fortechnical and professionalinterventionto benefit theagriculturalsectorin the area.